ANALISIS IMPLEMENTASI PENGELOLAAN PENERIMAAN NEGARA BUKAN PAJAK NIKAH ATAU RUJUK DI KEMENTERIAN AGAMA KABUPATEN SIGI - Ulyani, Ulyani (Katalogis, 2017)
This study aims to analyze Implementation Management of Non-Tax Revenues Nikah Or Refer (PNBP costs NR) as well as supporting and inhibiting factors in the Ministry of Religion Sigi. This type of research is qualitative data analysis was performed with an interactive model. The informants were officials and management staff in the scope of the Ministry of Religious Affairs and the Office of Sigi Regency in Central Sulawesi Province Ministry of Religious Affairs. The results showed that: (1) Management Implementation costs PNBP-NR Sigi implemented by the Ministry of Religion and organizers Sigi operations performed by KUA nine districts. In PNBP Management Policy Implementation NR fee, to factor in the dimension of the transformation of information communication goes well, but the dimensions of clarity and consistency remains a bottleneck. Factors Resources on the authority aspect looks very supportive with their suitability and delegation of authority implementor, but on the other hand are aspects of executive personnel and facilities remains a bottleneck. For Factor Disposition/Attitude, aspects of removal of bureaucratic/placement officers, support the commitment and transparency general manager of policy implementation management of non-tax cost of marriage or refer quite good but the incentive aspect there are still barriers and to factor Organizational Structure in the dimension of Standard Operating Procedures (SOP) and fragmentation It's going well.